Tuberculosis in the United States: Medical Consultation Services Provided by 5 Tuberculosis Regional Training and Medical Consultation Centers, 2013–2017. (4th April 2019) - Goswami, Neela D; Mase, Sundari; Griffith, David; Bhavaraju, Rajita; Lardizabal, Alfred; Lauzardo, Michael; Chen, Lisa; Wilson, John; Chappelle, Courtney; Haley, Connie A
Abstract: With only 9105 new US tuberculosis (TB) cases reported in 2017, expert consultation is essential for TB care. Data were captured 2013–2017 from consultations by 5 CDC-funded centers, now the TB Centers of Excellence (COEs). 14 586 consultations were provided to TB providers, most related to TB disease and treatment regimens.